Peran Pemerintah Daerah Dalam Pengembangan Wisata Perahu Kalimas di Kota Surabaya (Studi Pada Dinas Kebudayaan, Kepemudaan, dan Olahraga Serta Pariwisata Kota Surabaya) - Yoly, Danisa Putri; Pradana, Galih Wahyu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Surabaya City is one of the cities that has a variety of interesting tourism potentials to be developed. The Surabaya City Government through the Surabaya City Culture, Youth, Sports and Tourism Office (Disbudporapar) which has duties and functions in the tourism sector is trying to develop a fairly unique water tourism, namely the Kalimas Boat Tour. This tourist attraction is one of the priority tourism destinations regulated in the Surabaya City Regional Tourism Development Master Plan (RIPPDA) in 2023. This study aims to determine the role of the local government in developing Kalimas boat tourism in Surabaya City. The theory used in this study is the role theory according to Ilyas, (2014) in (Ndepi et al., 2024) which includes the role of the government as a facilitator, regulator, and dynamicator, as well as aspects of tourism development according to (Yoeti, 2008) which depend on 3A which includes Attraction, Accessibility, and Facilities. The research method used is descriptive with a qualitative approach. The research results show that local governments have carried out their roles optimally. As a facilitator, the local government has facilitated various forms of support provided. As a Regulator, the local government has set policies, and involved cross-sectoral. As a Dynamicator, the local government has involved communities, local business actors to participate in the development of Kalimas boat tourism.